Outcome of a giant coronary artery mycotic pseudoaneurysm secondary to non-typhoid Salmonella managed without surgical intervention. Issue 2 (13th February 2019) - Haque, Husham; Zohourian, Hajir
Abstract : A 48-year-old woman with a history of AIDS, a recent coronary artery bypass graft operation and prior bacteraemia with non-typhoid Salmonella presented with non-exertional chest pain and elevated troponins. The cardiac catheterisation and coronary CT angiography revealed a 9 cm pseudoaneurysm arising from the proximal left anterior descending artery. The blood cultures confirmed non-typhoid Salmonella . Emergent surgery was initially deferred due to her complex anatomy. Moreover, the hospital course was complicated by Epstein-Barr virus meningitis and an associated decline in the patient's mentation. Consequently, the mycotic pseudoaneurysm was medically managed with antibiotics and strict blood pressure goals. The natural history of giant mycotic coronary artery pseudoaneurysm formation and progression is appreciated through this first reported medically managed case. The follow-up coronary CT angiography at 3 months showed evidence of pseudoaneurysm leakage into surrounding tissue. The patient expired at 5 months from an unknown cause.